Age–Period–Cohort Analysis of Long Trend of Mortality for Stroke and Subtypes Attributed to High SBP in Chinese Adults - Ma, Yudiyang; Cao, Jinhong; Mubarik, Sumaira; Bai, Jianjun; Yang, Donghui; Zhao, Yudi; Hu, Qian; Yu, Chuanhua (Frontiers in Neurology, 2022)
Stroke has been found as the leading cause of death in China, and high systolic blood pressure (SBP) has been indicated as a critical risk factor of stroke mortality. Accordingly, in this article, the aims were to investigate the long-term trends of mortality in terms of stroke and subtypes arising from high SBP stratified by age and gender among Chinese adults. The data of this article originated from the global burden of disease (GBD) study database. The age, period, and cohort effects were examined with the age–period–cohort model (APC). The age-standardized mortality of stroke attributed to high SBP in China has been significantly declining from 1990 to 2019. As indicated by the result of APC analysis, substantially rising age effects have been exerted on stroke and subtypes from 25 to 84 years of both genders, whereas the age effect on women increased less rapidly than that on men. As opposed to the above result, the period and cohort effects were reported to show similar monotonous decrease trends, and stroke of women more significantly declined than that of men (significantly with p < 0.05 for all). All types of stroke mortality arising from high SBP were indicated to change. The risk of death was identified to be most remarkably reduced in high SBP-attributable subarachnoid hemorrhage (SAH), whereas intracerebral hemorrhage (ICH) and ischemic stroke (IS) decreased at approximately the same rate. People born in the later birth cohorts or living in recent periods had a lower risk of stroke death, whereas men and elder groups were considered as the high-risk populations for stroke mortality due to high SBP. Although the stroke mortality relating to high SBP in China was declining, ICH and IS would continue to be the first and second lethal subtypes of stroke. In contrast to the above finding, SAH accounted for the minimum proportion of deaths and the maximum reduction in period and cohort effects. Thus, it is of high significance to introduce advanced hypertension control technology and knowledge regarding healthy lifestyles.